Prototypes of masculine and feminine leadership in military population - Lupano Perugini, María Laura (2008)
The goal of the study was to identify masculine and feminine prototypes of effective leadership in military population. Data included 262 individuals, 69,5% (n = 182) male and 30,5% (n = 80) female (age average = 25,62 years). 66% of the participants directed other persons and 34% were subordinates. Data collection was carried out administering a survey designed ad-hoc. Participants were requested to name two effective leaders (man and woman) and to justify their election. They mainly identified male leaders with military people belonging not only to current military population but also those recognized because of their heroic feats. In relation with female leaders, subjects identified religious people, militaries belonging to current military population and politicians. We found differences in assigned characteristics to both prototypes.